Analysis Of Location Selection Using Center Of Gravity Method For Production Optimization (Case Study Of Sumedang Saribumi Karawang Tofu Factory) - Intan Nur Octaviani; Rediawan Miharja; Wardhana (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Determining the location of the factory is an important element so that the factory continues to develop and operate. The Sumedang Saribumi Karawang tofu factory has problems in the production process, during the continuous rainy season the factory experiences flooding so it has to close production and experiences increased transportation costs due to the distance between the factory and several distributors. relatively high operational cost barriers of IDR 43,650,000 per year. So, when selecting the right location it is necessary to avoid obstacles in the production process. Therefore, it is important to select a location using the Center Of Gravity method. Based on previous research, the Center of Gravity can produce distribution centers based on the location of the location to be addressed and the volume of delivery so as to produce optimal locations and the distribution process can be effective and efficient. This research method uses a quantitative descriptive approach with Center Of Gravity calculations. By conducting observations and interviews and collecting some of the document data needed for the research. The research results show the optimal location of the factory with coordinate points X (–6.418306, 107.388306). namely in the Cimahi, Klari, Karawang Regency areas. The total reduction in distance resulting from this research was reduced by 4 km. By reducing the total distance traveled, transportation costs will also be smaller. The location of the Sumedang Saribumi Karawang tofu factory which has been suggested is at several distributor locations and also the newest location tends to not experience flooding with the location being in an area with a good drainage system that can drain rainwater quickly and efficiently thereby reducing the risk of flooding. So the current location is an advantage that can be utilized by the Sumedang Saribumi Karawang tofu factory because the distribution process is the key to the success of distribution activities.